Gut Microbiome Dysbiosis and Its Impact on Reproductive Health: Mechanisms and Clinical Applications - Efthalia Moustakli; Sofoklis Stavros; Periklis Katopodis; Anastasios Potiris; Peter Drakakis; Stefanos Dafopoulos; Athanasios Zachariou; Konstantinos Dafopoulos; Konstantinos Zikopoulos; Athanasios Zikopoulos (Metabolites, 2025)
The human gut microbiome is integral to maintaining systemic physiological balance, with accumulating evidence emphasizing its critical role in reproductive health. This review investigates the bidirectional interactions between the gut microbiota and the female reproductive system, mediated by neuroendocrine, immune, and metabolic pathways, constituting the gut–reproductive axis. Dysbiosis, characterized by microbial imbalance, has been linked to reproductive disorders such as polycystic ovary syndrome (PCOS), endometriosis, infertility, impaired spermatogenesis, and pregnancy complications. These associations can be explained by immunological dysregulation, systemic inflammation, altered sex hormone metabolism, and hypothalamic–pituitary–gonadal (HPG) axis disturbances. This review aims to clarify the molecular and cellular mechanisms underpinning gut–reproductive interactions and to evaluate the feasibility of microbiome-targeted therapies as clinical interventions for improving reproductive outcomes.